Combinatorial optimization : methods and applications - NATO Advanced Study Institute Meeting on Combinatorial Optimization: Methods and Applications (2006 : Montreal, Quebec); Chvatal, Vasek, 1946-; NATO Emerging Security Challenges Division (Amsterdam ; Washington, D. C. : IOS Press)
Includes bibliographical references